Maintenance of Cotton Leaf Curl Multan Betasatellite by Tomato Leaf Curl New Delhi Virus—Analysis by Mutation - Iqbal, Zafar; Shafiq, Muhammad; Ali, Irfan; Mansoor, Shahid; Briddon, Rob W. (Frontiers in Plant Science, 2017)
Viruses of the genus Begomovirus (family Geminiviridae) are economically important phytopathogens that are transmitted plant-to-plant by the whitefly Bemisia tabaci. Most Old World (OW) begomoviruses are monopartite and many of these interact with symptoms and host range determining betasatellites. Tomato leaf curl New Delhi virus (ToLCNDV) is one of only a few OW begomoviruses with a bipartite genome (components known as DNA A and DNA B). Four genes [AV2, coat protein (CP), transcriptional-activator protein (TrAP), and AC4] of ToLCNDV were mutated and the effects of the mutations on infectivity, symptoms and the ability to maintain Cotton leaf curl Multan betasatellite (CLCuMuB) were investigated. Infectivity and virus/betasatellite DNA titer were assessed by Southern blot hybridization, PCR, and quantitative PCR. The results showed TrAP of ToLCNDV to be essential for maintenance of CLCuMuB and AV2 to be important only in the presence of the DNA B. AC4 was found to be important for the maintenance of CLCuMuB in the presence of, but indispensable in the absence of, the DNA B. Rather than being required for maintenance, the CP was shown to possibly interfere with maintenance of the betasatellite. The findings show that the interaction between a bipartite begomovirus and a betasatellite is more complex than just trans-replication. Clearly, multiple levels of interactions are present and such associations can cause additional significant losses to crops although the interaction may not be stable.